Attitűdváltozások a női munkavállalás megítélésében (Szociológiai Szemle, 2024)
The paper uses the Hungarian data of the International Social Survey collected in 1988 and 1994. One of the objectives of the survey was to get acquainted with the views related to female employment. The data show that opinions have moved in a conservative direction as a larger proportion of men as well as of women would approve of a reduction of female participation in the labour market. This is particularly so in the case of women caring for small children. The paper calls attention to the discrepancy existing between reality (the actual employment of women), opinion and attitudes.